Activation of invariant natural killer T cells impedes liver regeneration by way of both IFN‐γ‐ and IL‐4‐dependent mechanisms. Issue 4 (9th May 2014) - Yin, Shi; Wang, Hua; Bertola, Adeline; Feng, Dechun; Xu, Ming‐jiang; Wang, Yan; Gao, Bin
<x xml:space="preserve">Abstract</x> Invariant natural killer T (iNKT) cells are a major subset of lymphocytes found in the liver. These cells mediate various functions, including hepatic injury, fibrogenesis, and carcinogenesis. However, the function of iNKT cells in liver regeneration remains unclear. In the present study, partial hepatectomy (PHx) was used to study liver regeneration. α‐Galactosylceramide (α‐GalCer), a specific ligand for iNKT cells, was used to induce iNKT cell activation. After PHx, two strains of iNKT cell‐deficient mice, CD1d−/− and Jα281−/− mice, showed normal liver regeneration. Injection of α‐GalCer before or after PHx, which rapidly stimulated interferon‐gamma (IFN‐γ) and interleukin (IL)‐4 production by iNKT cells, markedly inhibited liver regeneration. In vitro treatment with IFN‐γ inhibited hepatocyte proliferation. In agreement with this in vitro finding, genetic disruption of IFN‐γ or its downstream signaling molecule signal transducer and activator of transcription (STAT)1 significantly abolished the α‐GalCer‐mediated inhibition of liver regeneration. In vitro exposure to IL‐4 did not affect hepatocyte proliferation, but surprisingly, genetic ablation of IL‐4 or its downstream signaling molecule STAT6 partially eliminated the inhibitory effect of α‐GalCer on liver regeneration. Further studies revealed that IL‐4 contributed to α‐GalCer‐induced iNKT cell expansion and IFN‐γ production, thereby inhibiting liver regeneration. Conclusion: iNKT cells play a minor role in controlling liver regeneration after PHx under healthy conditions. Activation of iNKT cells by α‐GalCer induces the production of IFN‐γ, which directly inhibits liver regeneration, and IL‐4, which indirectly attenuates liver regeneration by stimulating iNKT cell expansion and IFN‐γ production. (Hepatology 2014;60:1356–1366)